Unity in Malay family - Yaacob, H. (University of Malaya, 2005)
Unity within the family and kinship systems is the strongest, and it surpasses unity found in any other systems in human society. This is due to the fact that kinship is the basis of social structure, and relationships among kin and family members are key relationships in society. A person would first interact with his family members before he establishes any form of relationship with others in the society. It is only natural that family members help one another, organize activities together, and give priority and preference to one another at the expense of others (non-family members). The following discussion focuses on the underlying factors that foster family unity in Malay society. These include: kin grouping, residential patterns, marriage, property ownership, economic cooperation, as well as social and religious obligations.